CHARACTERISTICS OF ADOLESCENT, FAMILY, AND PARENTING STYLES ON SEXUAL VIOLENCE IN ADOLESCENTS - Dinda Ayu Safira Amatulah; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Violence is a case that teenagers often experience, and violence cases in Indonesia are increasing every year. This study aims to analyze how adolescent and family characteristics and parenting styles influence sexual violence in adolescents. The research design used a cross-sectional study, followed by 45 young women who had experienced sexual violence in several provinces in Indonesia. The data collection technique used voluntary sampling using google-form, distributed through social media. This study uses the Parental Acceptance Rejection (PARQ) and Child Sexual Abuse (CSA). The results showed that adolescents who experienced violence were in the age range of 13 to 18 years. Teenage fathers primarily work as labourers, and mothers do not work/IRT. Parental marital status in general, living in their own home and residing in rural areas. The style of acceptance, aggression, neglect, and rejection of parents is low. However, sexual violence against adolescents is severe, with the most frequent perpetrators of violence perpetrated by their peers. The results showed that parents whose status was married had a rejection style of parenting, and teenagers who did not have their bedroom felt more cared for. Adolescents who live with nuclear families and receive an accepting parenting style from their parents are less likely to experience sexual violence. Keywords: family characteristics, parenting style, sexual violence, teenagers